KERJA SAMA ORANG TUA DENGAN PENDIDIK DALAM PENDAMPINGAN BELAJAR ANAK USIA DINI SAAT PEMBELAJARAN DARING DI PAUD MARTUMBUR KEC. NASSAU - Samosir, Rotua; Hotmaria Panjaitan; Sharlin Elviyana Harefa (PRODI PKAUD, IAKN TARUTUNG, 2023)
Early childhood education plays a very important role in the formation of the basics of education and child development. In today's digital era, online education or distance learning has become an integral part of the learning process. However, the challenges faced by young children during online learning require close collaboration between parents and educators. The purpose of this journal is to investigate the role of parents and educators in assisting early childhood learning during online learning. The research method used in this journal is qualitative research. Data was collected through interviews with parents and early childhood educators involved in online learning. Data analysis was carried out through a thematic approach to identify general patterns and significant findings regarding collaboration between parents and educators. The results of the study show that cooperation between parents and educators has a significant positive impact on early childhood education during online learning. Parents have an important role as a child's learning companion at home. They can help facilitate a conducive learning environment, provide guidance, and support a child's learning motivation. Educators need to activate the role of parents by providing clear instructions, relevant learning resources, and open communication. In conclusion, cooperation between parents and educators is a key factor in assisting early childhood learning during online learning. Parents' active involvement in their child's education can increase the effectiveness of online learning and address the challenges faced by young children during distance learning. It is important for educators to facilitate this cooperation through open communication and providing the necessary support to parents.